The protocol for a multicentre prospective randomized noninferiority trial of surgical reduction versus non-surgical casting for displaced distal radius fractures in children: Children’s Radius Acute Fracture Fixation Trial (CRAFFT) protocol - Daniel C. Perry; Juul Achten; James Mason; Daphne Kounail; Nicolas Nicolaou; David Metcalfe; Mark Lyttle; Elizabeth Tutton; Duncan Appelbe; Phoebe Gibson; Matthew L. Costa (Bone & Joint Open)
Aims: The remarkable capacity for distal radius fractures in children to remodel raises questions about the necessity and extent of the intervention required to achieve anatomical alignment. The British Society of Children’s Orthopaedic Surgery prioritized this uncertainty as one of their most important research questions. This is the protocol for a randomized, controlled, multicentre, prospective, noninferiority trial of non-surgical casting versus surgical reduction for severely displaced fractures of the distal radius in children: the Children’s Radius Acute Fracture Fixation Trial. Methods: Children aged four to ten years old inclusive, who have sustained a severely displaced distal radius fracture, are eligible to take part. Baseline function using the Patient-Reported Outcomes Measurement Information System (PROMIS) Upper Extremity Score, pain measured using the Wong-Baker FACES Pain Scale, and quality of life (QoL) assessed with the EuroQol five-dimension questionnaire for younger participants will be collected. Each patient will be randomly allocated (1:1), stratified using a minimization algorithm by centre, fracture type at presentation (completely off-ended or incompletely off-ended), fracture location (metaphyseal or physeal), and age group (four to six years or seven to ten years) to either a regimen of non-surgical casting or surgical reduction. Conclusion: At six weeks, and three, six, and 12 months, data on function, pain, QoL, cosmesis, and satisfaction with care will be collected. After completion of the main phase of the study, patients will be followed up for a further two years. Up to one year after randomization, the main outcomes plus data on complications, resource use, and school absence will be collected. The primary outcome is the PROMIS Upper Extremity Score at three months post-randomization. All data will be obtained through electronic questionnaires completed by the participants and/or parents/guardians. Cite this article: Bone Jt Open 2025;6(5):560–568.